Graphite/Nanosilicon Composite Anode for Lithium‐Ion Capacitors with Improved Energy Density and Cyclability - Cheng Jie Chng; Yusuke Abe; Seiji Kumagai (Advanced Energy & Sustainability Research)
The current energy density of Li‐ion capacitors (LICs) is unfavorable for industrial applications, due to the asymmetrical electrochemical kinetics between the anode and cathode. Herein, the energy density of composite anode materials is increased by optimizing the mass ratio between graphite (Gr) and nano‐Si to enable the solid electrolyte interface (SEI) to effectively buffer the large volume changes of Si during lithiation/delithiation. A twice‐repeated prelithiation method is used to stabilize the SEI and eliminate the irreversible capacity of the composite anodes. Variation of the Gr:nano‐Si mass ratio of the composite anode from 0 to 40 mass% shows that, although the LIC with a Gr:nano‐Si mass ratio of 80:20 (Gr80Si20) exhibits the highest energy density (91.9 Wh kg−1), its energy density deteriorates drastically after 10 000 cycles, retaining only 34.8% of its initial energy density. Conversely, the LIC with the composite anode with a Gr:nano‐Si mass ratio of 60:40 (Gr60Si40) has slightly lower energy density (87.3 Wh kg−1) but demonstrates outstanding cycling performance with energy density retention of 87.2% after 10 000 cycles. These findings highlight the potential of incorporating Gr/nano‐Si composite anodes into LICs for high‐energy‐density industrial applications.